PERAN AGAMA DAN PENDIDIKAN AGAMA ISLAM SEBAGAI SOLUSI ALTERNATIF MENEMUKAN JATI DIRI TERHADAP ALIENASI DAMPAK MODERNISASI - Moh. Fachri (Nurul Jadid University, 2017)
Modernization is one manifestation of the causes of social change can lead to a very wide influence in various sectors of life. The influence of modernization in addition to a positive impact to ward progress, in fact, also gave rise to the negative effects of the inevitable. The form of the negative effects, for example; Alienation (Alienation). Alienation in the shape of a feeling of helplessness, meaningless, and feels remote / foreign environment and feeling less concerned about the lack berdayaaan others, the psychiatric symptoms should find an alternative solution to handling. Religion with the teachings and ceremonies/religious rituals offered to man to find his consciousness back as a whole human being, and feel the calmness and peace as well as provide motivation and encouragement to confront life, with all the attending problems. Similarly, Islam ic Religious Education (PAI) which is a conscious and deliberate effort to prepare them (students) to know, understand, appreciate, believe, berakhlaq noble, the teachings of the Islam ic religion from primary sources holy book of Qur’an and Alhadits through guidance, teaching, training, and administration experience.